2012
DOI: 10.1002/syn.21565
|View full text |Cite
|
Sign up to set email alerts
|

GABAB receptors do not internalize after baclofen treatment, possibly due to a lack of β‐arrestin association: Study with a real‐time visualizing assay

Abstract: The mechanism of agonist-induced GABA(B) receptor (GABA(B) R) internalization is not well understood. To investigate this process, we focused on the interaction of GABA(B) R with β-arrestins, which are key proteins in the internalization of most of the G protein-coupled receptors, and the agonist-induced GABA(B) R internalization and the interaction of GABA(B) R with β-arrestin1 and β-arrestin2 were investigated in real time using GABA(B) R and β-arrestins both of which were fluorescent protein-tagged. We then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Another potential mechanism of action is GABA B Ractivated internalization of the GABA B R-Ca v 2.2 complex. However, it was recently shown that b-arrestin, which is important for receptor internalization, is not bound to GABA B R (Sudo et al, 2012). Furthermore, surface biotinylation showed that GABA B R cell surface expression was not affected by exposure to Vc1.1 (Cuny et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Another potential mechanism of action is GABA B Ractivated internalization of the GABA B R-Ca v 2.2 complex. However, it was recently shown that b-arrestin, which is important for receptor internalization, is not bound to GABA B R (Sudo et al, 2012). Furthermore, surface biotinylation showed that GABA B R cell surface expression was not affected by exposure to Vc1.1 (Cuny et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…First, signal transduction by arrestins has gradually gained wider recognition through pioneering studies with a number of family A and family B 7TMRs over the last 15 years, but analogous evidence linking mGluRs and other family C 7TMRs with arrestins is limited: calcium sensing receptor and mGlu7 receptor function are sensitive to β-arrestin knockdown or overexpression323334, whereas GABA B receptors do not appear to associate with or initiate β-arrestin-mediated trafficking or signal transduction35. Second, in previous studies G protein-independent signalling has been associated experimentally with mGlu1 receptors rather than mGluR5 (ref.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, it has been shown that desensitization of GABA B receptors can occur through a phosphorylation-independent mechanism via GRK4 in HEK293 cells and cerebellar granule cells (Perroy, et al, 2003). Phosphorylation of D2 receptors by PKC results in desensitization and internalization of those receptors through β-arrestins (Namkung and Sibley, 2004; Thibault, et al, 2011), whereas it has been shown that baclofen stimulation of GABA B receptors does not result in internalization of that receptor, nor did it result in interaction with β-arrestins even in the presence of GRK4 (Sudo, et al, 2012). Despite the cross-desensitization between dopamine and baclofen in the present study, the mechanisms for desensitization for each receptor may be different.…”
Section: Discussionmentioning
confidence: 99%